Two New Antiprotozoal Diterpenes From the Roots of Acacia nilotica - Anyam, John V.; Daikwo, Priscilla E.; Ungogo, Marzuq A.; Nweze, Nwakaego E.; Igoli, Ngozichukwuka P.; Gray, Alexander I.; De Koning, Harry P.; Igoli, John O. (Frontiers in Chemistry, 2021)
The powdered roots of the medicinal plant Acacia nilotica were extracted with hexane and ethyl acetate and the extracts subjected to column chromatography for the isolation of potentially bioactive compounds and their screening against kinetoplastid pathogens. NMR and HREI mass-spectrometric analyses identified two new diterpenes, characterized as 16, 19-dihydroxycassa-12-en-15-one (Sandynone, 1) and (5S, 7R, 8R, 9R, 10S, 13Z, 17S)-7,8:7,17:16,17-triepoxy-7,8-seco-cassa-13-ene (Niloticane B, 2). Also isolated were the previously reported (5S,7R,8R,9R,10S) -(-)-7,8-seco-7, 8-oxacassa-13,15-diene-7,17-diol (3), (5S,7R,8R,9R,10S) -(-)-7,8-seco-7, 8-oxacassa-13,15-dien-7-ol-17-al (4) and (5S,7R,8R,9R,10S) -(-)-7,8-seco-7, 8-oxacassa-13,15-dien-7-ol (5). A mixture of stigmasterol (6a) and sitosterol (6b), as well as lupeol (7) were also isolated. Several column fractions displayed significant activity against a panel of Trypanosoma and Leishmania spp and from the most active fraction, compound 4 was isolated to high purity. The compound displayed high activity, particularly against T. brucei, T. evansi and L. mexicana (0.88 - 11.7 µM) but only a modest effect against Human Embryonic Kidney cells, and no cross-resistance with the commonly used melaminophenyl arsenical and diamidine classes of trypanocides. The effect of compound 4 against L. mexicana promastigotes was irreversible after a 5-h exposure, leading to the sterilization of the culture between 24 and 48 h.